Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb. - Pitts, James P.; Waichert, Cecilia; Sadler, Emily (Zootaxa, 2017)
The genus Dicranoplius Haupt is reviewed and is treated as a subgenus of Anoplius, new comb., based on morphological and molecular evidence. This subgenus contains Anoplius albidus (Evans), A. areatus (Taschenberg), A. brevitarsus (Banks), A. cujanus (Holmberg), A. diphonichus (Spinola), A. nigritus (Evans), A. pampero (Evans), A. satanus (Holmberg), and A. evansi, sp. nov., newly described here from Colombia. Dicranoplius stangei Evans is considered a junior synonym of A. areatus (Taschenberg).